A study on the jurisdiction and efficiency of the Malaysian Anti-Corruption Commission (MACC) in combating corruption / Mohamad Radzwill Abdullah - Abdullah, Mohamad Radzwill (2012)
The purpose to reform the then Anti-Corruption Agency (ACA) into Malaysian Anti-Corruption Commission (MACC) is to enhance the effectiveness and efficiency of its anti-corruption efforts as well as to improve perception of independence and transparency of the functions of the Commission (2009 MACC Annual Report). However despite 4 years of formation of MACC, the Corruption Perception index (CPI) by Transparency International (TI) shows Malaysia's ranking slipping away from number 56 in year 2009 to number 60 in year 2011. The Auditor's General Report 2011 that was just published shows possible corruption in the public sector, which does not portray MACC in a credible position. Is it true that the new act, Malaysia Anti-Corruption Commission Act 2009 does give the Commission more autonomy and power so that they can execute their operation independently and in a more effective manner? Hence, this research, studies the differences of the jurisdiction power between Anti-Corruption Act 1997 and Malaysia Anti-Corruption Commission Act 2009. This research also studies the volume of cases recorded, investigated and solved during the time of ACA and its successor MACC. The result shows that there is no autonomy given to MACC. MACC still have the same reporting line as ACA. MACC still do not have the legislative authorization to prosecute. This inadequacy, in tum will portray the image of MACC as ineffective and weak. However certain power to expedite and ease the investigation has been handed to MACC, which before, need to be authorized by the Public Prosecutor. The volume of cases recorded, investigated and solved shows a mixed result. Some key information are not reported in the MACC Annual Report which has been reported in the ACA Annual Report. However, there is an improvement in terms of cases that is classified as 'no further action' where the numbers has gone down. Numbers of arrest in giving gratification has also improved parallel to the ·numbers of arrest in accepting gratification.